Role of BAG5 in Protein Quality Control: Double-Edged Sword? - Gupta, Manish K.; Randhawa, Puneet Kaur; Masternak, Michal M. (Frontiers in Aging, 2022)
Cardiovascular disorder is the major health burden and cause of death among individuals worldwide. As the cardiomyocytes lack the ability for self-renewal, it is utmost necessary to surveil the protein quality in the cells. The Bcl-2 associated anthanogene protein (BAG) family and molecular chaperones (HSP70, HSP90) actively participate in maintaining cellular protein quality control (PQC) to limit cellular dysfunction in the cells. The BAG family contains a unique BAG domain which facilitates their interaction with the ATPase domain of the heat shock protein 70 (HSP70) to assist in protein folding. Among the BAG family members (BAG1-6), BAG5 protein is unique since it has five domains in tandem and the binding of BD5 induces certain conformational changes in the nucleotide-binding domain (NBD) of HSP70 such that it loses its affinity for binding to ADP and results in enhanced protein refolding activity of HSP70. In this review, we shall describe the role of BAG5 in modulating mitophagy, endoplasmic stress, and cellular viability. Also, we have highlighted the interaction of BAG5 with other proteins, including PINK, DJ-1, CHIP, and their role in cellular PQC. Apart from this, we have described the role of BAG5 in cellular metabolism and aging.